Review: Protestants and the Cult of the Saints in German-Speaking Europe, 1517–1531 - Brooks, Peter Newman (The journal of theological studies, 2005)
Protestants and the Cult of the Saints in German-Speaking Europe, 1517–1531 Carol Piper Heming xiv + 170 (Sixteenth-Century Essays and Studies, 65.)Kirksville, MO Truman State University Press 2003 1 931112 23 1 and 24 X Hardback$48.95 paper